PENYULUHAN HUKUM PENINGKATAN KAPASITAS APARAT DESA DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Bire, Chatryen M Dju; Nubatonis, Orpa Juliana; Tallo, Daud Dima; Jacob, Yossie M Y; Ermalinda, Jenny; Dollu, Daud Yaferson (Jurnal Abdi Insani, 2024)
Villages are a part of the Indonesian government that has a strategic role and function to assist the country's development. Despite this, many villages still face many problems related to public services, village financial management, low community participation in development, and a lack of legal understanding of good village management and governance according to applicable regulations, one of which is O'A Mate Village. To enable villages to develop and provide much better services to the community, efforts are needed to improve the capacity of village officials. This capacity building training for village officials was conducted in O'A Mate Village, Northwest Alor Sub-District, Alor Regency, and aimed to improve the knowledge and skills of village officials in the management of village governance and development, especially related to Law No. 6/2014 on Villages and the value of having good behavior. This community service activity was carried out in O'A Mate Village, Northwest Alor District, Alor Regency. The method used in this socialization is by means of face-to-face / lecture, discussion or in-depth dialogue about the material that has been presented with the participants. During the socialization, participants were quite active in asking questions about the material presented by the resource person. This was shown by active discussions and questions and answers between participants and resource persons. According to some participants, this activity showed that they had gained knowledge and understanding of the importance of increasing the capacity of village officials in carrying out their duties and responsibilities as village officials in accordance with Law No. 6/2014 on Villages. The participants acknowledged that the material presented by the service to society team was new and had never been heard or known by the community about the value of BeRAKHLAK in performing services as village officials. Finally, the service to society team can conduct socialization to improve the insights, knowledge and skills of village officials on how to manage village governance and development in a better way.